How well do first year university students learn to use multiple representations of physics concepts for understanding and problem solving ? - Treagust, David; Kuo, Yen-Ruey; Won, Mihye; Siddiqui, Salim; Zadnik, Marjan (World Conference on Physics Education, 2012)
Students who complete physics courses need to have demonstrated the achievement of a number of prescribed course learning outcomes such as knowledge of fundamental physics concepts and principles and application of those physics principles to understand the causes of problems, devise strategies to solve them, and test the possible solutions. What is not usually explicitly taught, though implicitly expected of students enrolled in physics, is the ability to use multiple representations (e.g. descriptions using words, diagrams, equations or formulae, and graphs) of fundamental physics concepts and to be able to understand and link different representations and hence develop a deeper understanding of the physics concepts. To teach effectively using multiple representations, it is necessary to explicitly present students with different forms of these representations. This presentation will describe a case study involving 150 first year university students in a physics course for non-majors. Two questionnaires on Thermal Physics and Optics were developed to assess students ‘conceptual understanding and their use of multiple representations to explain the concepts. We also conducted interviews to link students’ explanations to their responses in the questionnaire items. Two research questions guided the study: 1) How and to what extent do students use different representations to learn and communicate their understanding of physics concepts? and 2) How do different representations help students build deeper understanding of physics concepts?The results showed that even with explicit teaching, learning physics using multiple representations is difficult for these non-physics majors, and a large number of the students were unable to apply all four representations effectively to solve physics problems. Nevertheless with increased guided instruction, students were able to demonstrate more multiple representations and their connectedness. For physics instructors who want to assist students’ improvement of their conceptual understanding, this study has shown that it is necessary to systematically and explicitly introduce the different representations in lectures, tutorials and assessment.